Water management in a passive direct methanol fuel cell - Oliveira, V. B. (2013)
Passive direct methanol fuel cells (DMFCs) are under development for use in portable applications because of their enhanced energy density in comparison with other fuel cell types. The most significant obstacles for DMFC development are methanol and water crossover because methanol diffuses through the membrane generating heat but no power. The presence of a large amount of water floods the cathode and reduces cell performance. The present study was carried out to understand the performance of passive DMFCs, focused on the water crossover through the membrane from the anode to the cathode side. The water crossover behaviour in passive DMFCs was studied analytically with the results of a developed model for passive DMFCs. The model was validated with an in-house designed passive DMFC. The effect of methanol concentration, membrane thickness, gas diffusion layer material and thickness and catalyst loading on fuel cell performance and water crossover is presented. Water crossover was lowered with reduction on methanol concentration, reduction of membrane thickness and increase on anode diffusion layer thickness and anode and cathode catalyst layer thickness. It was found that these conditions also reduced methanol crossover rate. A membrane electrode assembly was proposed to achieve low methanol and water crossover and high power density, operating at high methanol concentrations. The results presented provide very useful and actual information for future passive DMFC systems using high concentration or pure methanol.